COVID-19 and capitalism : success and failure of the legal methods for dealing with a pandemic - Byttebier, K. (Koen) (Economic and financial law & policy (shifting insights & values) ;, 2022)
"This book provides an analysis of the socioeconomic determinants of COVID-19. From the end of 2019 until presently, the world has been ravaged by the COVID-19 pandemic. Although the cause of this is (obviously) a virus, the extent to which this virus spread, and therefore the number of infections and deaths, was largely determined by socio-economic factors. From this, it follows that the course of the pandemic varies greatly from one country to another. This observation applies both to countries' resilience to such a pandemic (which is mainly rooted in the period preceding the outbreak of the virus) and to the way in which countries have reacted to the virus (including the political choices on how to respond). Meanwhile, research has made it clear that the nature of this response (e.g., elimination policy, mitigation policy, and proceeding herd immunity) was, on the one hand, strongly determined by political and ideological factors and, on the other hand, was highly influential in the factors of success or failure in combating the pandemic. The book focuses on the situation in a number of Western regions (notably the USA, the UK, and the EU and its member states). The author addresses the reasons why in many Western countries both pandemic prevention and response policies to COVID-19 have failed. The book concludes with recommendations concerning the rearrangement of the socio-economic order that could increase the resilience of (Western) societies against such pandemics"--Adapted from the publisher's description.